2021
DOI: 10.31295/ijhms.v4n1.1533
|View full text |Cite
|
Sign up to set email alerts
|

E-Module development for midwifery care of childbirth first stage on partograph documentation system success improvement

Abstract: Purpose: This study aims to determine the effect of the e-module of childbirth on the success of the partograph documentation system of midwifery DIII students using the Magguru application. Methods: This study uses a Quasi Experiment method. The number of samples was 90 people who were taken using total sampling technique. This design observation is carried out twice, namely before the treatment is carried out and according to the treatment. Data analysis used the Wilcoxon test to determine the effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Based on the partograph filling checklist, it can be seen that students can fill in precisely the amniotic state (100%), DJJ (98.3%), write the opening time (94.8%), checking blood pressure (94.8%), decreasing the fetal head (93.1%), infiltrating the fetal head (93.1%) and filling at time 2 (91.4%). Partographs must be filled in completely because partographs have the main objectives, namely: Recording observations and assessing the progress of labor partographs can detect whether labor is normally going or there are irregularities, therefore by filling in the partograph completely and precisely it can do early detection of any possibility of old partus (Jusmawati et al, 2021;Manna et al, 2022;Silfia, 2020). Based on statistical tests, it was found that there was a difference in the average value of filling in the partograph of midwifery students before and after using the partograph guidebook, which was 66.10 and 81.41, which can be seen that there was an increase in the value of midwifery students in filling out the partograph with the difference in the increase in scores, namely previously the average value of 66.10 to an average of 81.41, which had a difference in values of 15.31, this increase was felt to be very significant and good.…”
Section: 1partograph Filling Before Partograph Pocket Book Exposurementioning
confidence: 99%
“…Based on the partograph filling checklist, it can be seen that students can fill in precisely the amniotic state (100%), DJJ (98.3%), write the opening time (94.8%), checking blood pressure (94.8%), decreasing the fetal head (93.1%), infiltrating the fetal head (93.1%) and filling at time 2 (91.4%). Partographs must be filled in completely because partographs have the main objectives, namely: Recording observations and assessing the progress of labor partographs can detect whether labor is normally going or there are irregularities, therefore by filling in the partograph completely and precisely it can do early detection of any possibility of old partus (Jusmawati et al, 2021;Manna et al, 2022;Silfia, 2020). Based on statistical tests, it was found that there was a difference in the average value of filling in the partograph of midwifery students before and after using the partograph guidebook, which was 66.10 and 81.41, which can be seen that there was an increase in the value of midwifery students in filling out the partograph with the difference in the increase in scores, namely previously the average value of 66.10 to an average of 81.41, which had a difference in values of 15.31, this increase was felt to be very significant and good.…”
Section: 1partograph Filling Before Partograph Pocket Book Exposurementioning
confidence: 99%